2021
DOI: 10.1017/s1049096520001742
|View full text |Cite
|
Sign up to set email alerts
|

Learning through Peer Reviewing and Publishing in the Pi Sigma Alpha Undergraduate Journal of Politics: Twenty Years Later

Abstract: The Pi Sigma Alpha Undergraduate Journal of Politics (PSAJ), sponsored by the Pi Sigma Alpha National Honor Society, was founded in 2001 at Purdue University. After 20 years, much has changed in undergraduate research and publishing, but the benefits of producing a peer-reviewed journal remain the same. Undergraduate research has increased in prominence, and the journal has modernized to meet these transformations. This article describes the history, purpose, and operations of the PSAJ. Most important, a surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Previous studies have shown that experience produces more critical peer reviewers (Nylenna, Riis, and Karlsson 1994). This is consistent with responses from former editorial board members who, when asked to describe their experience, stated that their tenure aided in their discussion and analytical skills and motivated some to create their own research and to enter academia (Walker et al 2021).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Previous studies have shown that experience produces more critical peer reviewers (Nylenna, Riis, and Karlsson 1994). This is consistent with responses from former editorial board members who, when asked to describe their experience, stated that their tenure aided in their discussion and analytical skills and motivated some to create their own research and to enter academia (Walker et al 2021).…”
Section: Discussionsupporting
confidence: 76%
“…As acknowledged by political science departments and academic conferences, undergraduate research plays an increasingly critical role in the political science discipline (Cox and Kent 2018; Walker et al 2021). Along with the increase in undergraduate research is an increase in undergraduate journals that publish this research and are commonly run by undergraduate editorial boards and leadership.…”
Section: An Increase In Undergraduate Journalsmentioning
confidence: 99%
See 3 more Smart Citations